Washington View: Money, power, and education. (May 2019) - Ferguson, Maria
Three news stories from spring 2019 put the spotlight on the interaction between money, power, and political influence in education. The Varsity Blues scandal, in which 50 people were charged with using bribes, false test scores, and other shady methods to influence college admission decisions, highlights not just the pernicious influence on money in higher education but also the false notion that certain schools are so special the mere act of attending can set its students up for a happy and successful life. President Donald Trump's fiscal year 2020 budget preserved funding for popular programs but cut programs for teacher professional development and federal student aid for higher education. And new research by Frederick Hess and Jay Greene reveals that the education reform and research movements are populated by a large proportion of supporters of Democratic candidates .